The effects of topical application of red pomegranate (Punica granatum Linn) extract gel on the healing process of traumatic ulcers in Wistar rats - Sri Hernawati; Yonanda Az Zikra; Dwi Warna Aju Fatmawati (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Trauma-induced ulcers constitute one of the painful abnormalities affecting the oral cavity about which numerous individuals complain. The prevalence of traumatic ulcers (15-30% of cases) is relatively high compared to other oral lesions. Unfortunately, the use of anti-inflammatory drugs classified as steroids can lead to contraindications and serious side effects. Hence, the use of natural ingredients represents an alternative treatment. One such ingredient is red pomegranate containing bioactive elements acting as anti-inflammatory, antibacterial, antimicrobial, and antioxidant agents which accelerate the healing process in traumatic ulcers. Purpose: The aim of this study was to determine the effects of the topical application of red pomegranate (Punica granatum Linn) extract on the healing process in traumatic ulcers in Wistar rats. Methods: 24 male rats, aged 2-3 months, were divided into six groups, namely; two control groups (PC: triamcinolone acetonide and NC: sterile aquades) and four treatment groups (red pomegranate extract gel at respective concentrations of 12.5%, 25%, 50% and 75%). A traumatic ulcer was subsequently created using a flame-shaped burnisher tip 2mm in diameter and heated for ±15 seconds. The diameter traumatic ulcer of each research subject was measured and observed until it healed within the remedial parameters determined by means of a UNC-15 periodontal probe which had been placed on it. The data obtained was analyzed using Kruskal-Wallis and Mann-Whitney tests. Results: Topically applied red pomegranate extract gel can reduce the width of the ulcerated area, while also accelerating traumatic ulcer healing. There was a significant difference in the healing time between the group using red pomegranate extract gel at a concentration of 75% and the positive control group using 0.1% triamcinolone acetonide with p=0.44 (p<0.05). Conclusion: Red pomegranate extract gel possesses the ability to accelerate the healing process in traumatic ulcers. The most effective concentration of red pomegranate extract gel at accelerating the healing process in traumatic ulcers is 75%.